Khapra Beetle, Trogoderma granarium Everts (Insecta: Coleoptera: Dermestidae) - Donny L. Harris (EDIS)
EENY-372, a 4-page illustrated fact sheet by D.L. Harris, describes one of the most feared stored-product pests in the world. It provides information about synonymy, identification, biology, economic importance, detection and management of this invasive beetle. Includes selected references. This publication has been published as DPI Entomology Circular 262 and is also available on the Featured Creatures Web site by the UF Department of Entomology and Nematology, May 2006.